PowToon Up Your Speaking: Engaging EFL Students with Interactive Presentations - Fadhilah, Auliyatul; Rahmadi Nirwanto; Hesty Widiastuty (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2024)
This study is aimed to develop English learning media by implementing the PowToon application as a speaking learning medium. The problem in this study is based on students' difficulty in developing their ability in speaking English, and they also want learning with technology-based media. Based on the speaking material demands of the students, the researcher developed educational materials. Specifically, they created animated video utilizing the PowToon application. The participants of this study were 28 (Twenty-eight) students of class XI Business Online Marketing (BDP) SMK Karsa Mulya, Palangka Raya. In this study, the design and development research method were used. Researchers develop media by applying analysis, design, development, implementation, and evaluation (ADDIE). The development was based on questionnaires, interviews, and expert validation. The results of this study based on the result of assessment materials expert obtained a percentage of 93.96% with very good qualifications, while based on the assessment of media experts obtained a percentage of 88.6% with very good qualifications. The findings of the current study are useful for both the teacher and the students, as well as have theoretical and practical implications for the teaching and learning of English, particularly in English teaching. Theoretically, the results of this study gave knowledge and implementation of the field of language science, especially ETMD (English Teaching Media Development), and TELL (Technology enhanced Language Learning) on acquiring English and give solutions to find out the appropriate media in teaching speaking. Practically, the result of the study is that using PowToon as a learning medium to teach English can improve students' speaking skills in terms of communication.